Small family firms' efforts to cope with the external disruption - the case of chinese traditional and complementary medicine (T&CM) practitioners - 582598 Ong, Eng Chuan; Abu Saim Md. Shahabuddin, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2012)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2012